Participatory Varietal Evaluation of Rainy Season Tomato under Plastic House Condition - Pandey, YR; Pun, AB; Upadhyuy, KP (Nepal Agriculture Research Journal, 2009)
Four tomato varieties namely LTH-61, Avinash-2, NSITH-162 and BL-410 were evaluated in farmer’s field with farmers participation under plastic house condition for yield potential and other yield characters at Hemja, Kaski (920 masl) during rainy seasons of two consecutive years 2002 and 2003. The experiment was arranged in randomized complete block design with 5 replications, farmer as a replication. NSITH-162 took the shortest period of days to flowering and first harvest with an average of 36 and 66 days after transplanting respectively. Fruit set after flowering was highest in NSITH-162 (93.9%) and the lowest in Avinash-2 (83.1%). NSITH-162 produced the highest marketable fruit yield (89.05 t/ha) and Avinash-2 produced the lowest (51.98 t/ha). The results of the experiment revealed that the hybrid varieties NSITH-162 and LTH-61 have more yield potentiality than open pollinated variety BL-410 and Avinash-2 an Indian hybrid variety and therefore NSITH-162 variety could be recommended for commercial production under plastic house condition. Key words: Participatory; plastic house; rainy season; tomato DOI: 10.3126/narj.v7i0.1860 Nepal Agriculture Research Journal Vol.7 2006 pp.11-15